The human factor in contemporary organisations and changes in modern technology - Szelągowska-Rudzka, Katarzyna; Mackiewicz, Hanna; Spodarczyk, Edyta (Zielona Góra: Faculty of Economics and Management Press)
The development of technology, the increasingly widespread use of its achievements prompt reflection on the role and importance of the human factor in contemporary organisations. The question arises: Will machines replace humans, or are humans more important than the products of modern technology?
Keywords: human factors; organizational models; Industry 4.0; ICT technology; social and technical subsystems of the organization